CoFe2O4 as a source of Co(II) ions for imidacloprid insecticide oxidation using peroxymonosulfate: Influence of process parameters and surface changes - Broterson, Yoisel B. (2024)
Nanometric cobalt magnetic ferrite (CoFe2O4) synthesized by distinct methods was used for in situ chemical activation of peroxymonosulfate (PMS) under neutral conditions to oxidize imidacloprid (IMD) insecticide. The effect of CoFe2O4 load (0.125–1.0 g L−1) and PMS concentration (250–1000 μM) was investigated as well as the influence of phosphate buffer and Co(II) ions. PMS activation by Co(II) ions, including those leached from CoFe2O4 (>50 μg L−1), exhibited a strong influence on IMD oxidation and, apparently, without substantial contributions from the solid phase. Within the prepared solid materials (i.e., using sol-gel and co-precipitation methods), high oxidation rates (ca. 0.5 min−1) of IMD were attained in ultrapure water. Phosphate buffer had no significant influence on the IMD oxidation rate and level, however, its use and solution pH have shown to be important parameters, since higher PMS consumption was observed in the presence of buffered solutions at pH 7. IMD byproducts resulting from hydroxylation reactions and rupture of the imidazolidine ring were detected by mass spectrometry. At optimum conditions (0.125 g L−1 of CoFe2O4 and 500 μM of PMS), the CoFe2O4 nanoparticles exhibited an increase in the charge transfer resistance and an enhancement in the surface hydroxylation after PMS activation, which led to radical (HO● and SO4●–) and nonradical (1O2) species. The latter specie led to high levels of IMD oxidation, even in a complex water matrix, such as simulated municipal wastewater at the expense of one-order decrease in the IMD oxidation rate.